Exploring the Impact of Virtual Reality Experiences on Tourist Behavior and Perceptions - Husni Teja Sukmana; Jong Il Kim (International Journal Research on Metaverse, 2024)
This study explores the impact of virtual reality (VR) experiences on tourist behavior and perceptions, utilizing logistic regression and analysis of variance (ANOVA) to understand these relationships. The logistic regression analysis revealed that VR experience (coefficient = 0.432, p = 0.020) significantly enhances the likelihood of being a tourist. Demographic factors such as gender (coefficient = -0.512, p = 0.018), income (coefficient = -0.301, p = 0.001), and age (coefficient = 0.298, p = 0.003) also play crucial roles: females and higher-income individuals are less likely to be tourists, while older individuals are more likely to travel. ANOVA results indicated significant differences in emotional responses (EMO1: F = 6.40, p = 0.012; EMO2: F = 4.63, p = 0.032; EMO3: F = 7.77, p = 0.006; EMO4: F = 5.77, p = 0.017), flow states (FLOW1: F = 12.21, p = 0.001; FLOW2: F = 20.39, p < 0.001; FLOW3: F = 17.38, p < 0.001; FLOW4: F = 14.52, p < 0.001), and intentions to visit (INT2: F = 7.79, p = 0.006; INT4: F = 4.61, p = 0.032) based on VR experience. These findings suggest that VR significantly influences emotional and cognitive states, fostering engagement, satisfaction, and increased intentions to visit real-world destinations. The results underscore the potential of VR as a powerful tool in tourism marketing, capable of driving tourism interest and behavior. Future research should investigate the long-term effects of VR on tourist behavior and consider cultural and technological advancements to further optimize VR's application in tourism. This study offers actionable insights for tourism marketers to develop targeted, effective, and immersive VR promotional strategies.